THE USE OF CLUSTERING TECHNIQUE IN TEACHING WRITING NARRATIVE TEXT - Meliya Adriati (Journal of English and Education, 2013)
This study investigated the use of clustering technique in teaching writing narrative text. Thus its specific objective was to find out: (1) whether the use of clustering technique is effective in teaching writing narrative text, and (2) the response of the students to this technique. The research method used in this study was quasi-experimental and the sample was sixty ten-graders in one senior high school in Bandung. Based on data from pre-test, post-test and interview, clustering technique was effective in improving students’ score in writing narrative text. Also, students’ response to the technique was positive as clustering had several strengths though it had several weaknesses too. Keywords: Clustering technique, narrative text